The role of humanitarian NGO's: impact on South Korean food aid policy towards North Korea from 1995 to 2007 - Moon, Kyung Yon (Cranfield University, 2011)
The existing literature has provided only a partial explanation of the political role of South Korean humanitarian non-governmental organisations (NGOs) in government food aid policy making towards North Korea between 1995 and 2007. Using a constructivist approach which includes non-state actor and normative factors in the analysis of state policy making, this thesis demonstrates that South Korean humanitarian NGO advocacy was consequential in explaining changes in South Korea’s food aid policy making in respect of state agenda setting, the formation of a discursive position and institutional and policy development. Humanitarian NGO advocacy finally contributed to government establishment of a legal framework that could provide for more consistent and large scale food aid to North Korea, irrespective of the vagaries of inter-Korean political relations. Despite humanitarian NGO advocacy, however, changes at different stages of state food aid policy making differed among the three administrations. This thesis demonstrates that these differences were attributable to the differing abilities of NGO to set agendas, network and graft new norms in respect of government policy on food aid to North Korea. These differing abilities resulted from changes in organisational mandates, funding capacities and the expertise of NGOs over time. Firstly, a strong humanitarian mandate between 1995 and 2000 was a key factor that enabled NGOs to overcome the organisational limits that stemmed from their poor funding capacity and lack of expertise. Secondly, stable funding capacity contributed to improvements in organisational expertise; however, increased reliance on government funding after 2000 resulted in the weakening of NGOs’ advocacy ability. Lastly, given the favourable operational environment after the Inter-Korean Summit in 2000, the organisational expertise of NGOs developed to a level where it was possible to exert direct influence on government food aid policy making towards North Korea.